Students’ Performance on Inquiry-Based Physics Instruction through Virtual Simulation - Eviota, John Salazar; Liangco, Minnie Maliwat (FKIP Universitas Lampung, 2020)
The main goal of this study was to prove the effect of inquiry-based instruction through virtual simulation on students’ performance in Physics. Three heterogeneous classes at grades seven with 141 students participated in the research, and a quasi-experimental design with pretest and posttest was used. The participants were divided into three groups for the three different teaching strategies, such as; inquiry-based instruction, virtual simulation, and inquiry-based instruction through virtual simulation taught by the same teacher. The pretest and posttest scores of the three groups were analyzed using comparative analysis, an F-test to determine if there is a significant difference in the students’ performance in learning the Physics concept before and after applying the inquiry-based method and virtual simulation strategy of teaching. The same was used to compare the difference between their performance before and after using inquiry-based instruction through virtual simulation. The findings revealed that inquiry-based instruction caused satisfying acquisition of scientific concepts related to content taught in Physics. The outcomes also supported that all the three teaching strategies have a highly notable effect on the students’ performance in Physics. As a result, the inquiry-based instruction through virtual simulations had a potential to help grade seven students improve their performance in Physics. Keywords: inquiry-based instruction, virtual simulations, Physics teaching. DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp22-34